Os efeitos da Lei de Responsabilidade Fiscal no endividamento municipal: uma análise para o Estado do Piauí - Borges, Glenda Santos de Almeida (2010)
The Fiscal Responsibility Law - LRF demand in its core print austerity when the realization of public spending. Its purpose is to balance the spending by printing in its context a new fiscal perspective. Based on this scenario objective with this research to develop an assessment on the effects of LRF on municipal indebtedness, based on data from the municipalities of Piauí created before 1997. The analytical criterion to verify the relationship of the LRF established in 2000, with the municipal debt before and after its advent. The methodology for assessing these scenarios is a structured literature review presenting the situation discussed related to the theme, talking about the variables involved, and an aggregate econometric model representing important government revenue that explain the indebtedness of municipalities. The study suggests that Piauí’s municipalities reduced its indebtedness by approximately 7% after the implementation of the LRF.